Igf1 Regulates Fibrocartilage Stem Cells, Cartilage Growth, and Homeostasis in the Temporomandibular Joint of Mice. (13th February 2023) - Bi, Ruiye; Luo, Xueting; Li, Qianli; Li, Peiran; Li, Haohan; Fan, Yi; Ying, Binbin; Zhu, Songsong
ABSTRACT: Temporomandibular joint (TMJ) growth requires orchestrated interactions between various cell types. Recent studies revealed that fibrocartilage stem cells (FCSCs) in the TMJ cartilage play critical roles as cell resources for joint development and repair. However, the detailed molecular network that influences FCSC fate during TMJ cartilage development remains to be elucidated. Here, we investigate the functional role of Igf1 in FCSCs for TMJ cartilage growth and homeostasis by lineage tracing using Gli1‐CreER + ; Tm flfl mice and conditional Igf1 deletion using Gli1‐/Col2‐CreER + ; Igf1 fl/fl mice. In Gli1‐CreER + ; Tm flfl mice, red fluorescence + (RFP + ) FCSCs show a favorable proliferative capacity. Igf1 deletion in Gli1 + / Col2 + cell lineages leads to distinct pathological changes in TMJ cartilage. More serious cartilage thickness and cell density reductions are found in the superficial layers in Gli1‐CreER + ; Igf1 fl/fl mice. After long‐term Igf1 deletion, a severe disordered cell arrangement is found in both groups. When Igf1 is conditionally deleted in vivo, the red fluorescent protein‐labeled Gli1 + FCSC shows a significant disruption of chondrogenic differentiation, cell proliferation, and apoptosis leading to TMJ cartilage disarrangement and subchondral bone loss. Immunostaining shows that pAkt signaling is blocked in all cartilage layers after the Gli1 + ‐specific deletion of Igf1 . In vitro, Igf1 deletion disrupts FCSC capacities, including proliferation and chondrogenesis. Moreover, the deletion of Igf1 in FCSCs significantly aggravates the joint osteoarthritis phenotype in the unilateral anterior crossbite mouse model, characterized by decreased cartilage thickness and cell numbers as well as a loss of extracellular matrix secretions. These findings uncover Igf1 as a regulator of TMJ cartilage growth and repair. The deletion of Igf1 disrupts the progenitor capacity of FCSCs, leading to a disordered cell distribution and exaggerating TMJ cartilage dysfunction. © 2023 American Society for Bone and Mineral Research (ASBMR).